Cytological screening and management of abnormalities in prevention of cervical cancer: an overview with stochastic modelling. Issue 5 (May 1994) - Sherlaw-Johnson, C; Gallivan, S; Jenkins, D; Jones, M H
Abstract : AIMS--To develop a mathematical model of the histological changes of precancer and the development of invasive cancer and how these are related to cytological findings. To use this to investigate the effects on incidence of cervical cancer, number of smear tests and colposcopies, of different schedules for cervical screening, and the clinical management policies for dyskaryosis. METHODS--A stochastic model was developed relating the available data on tissue progression to the cytological findings. Two strategies, A and B, were compared: under A, women with any abnormal smear receive immediate colposcopy and treatment; under B, women with mild or borderline dyskaryosis have repeated smears at six monthly intervals with colposcopy only for persistent abnormalities. RESULTS--The model predicted an incidence of invasive cervical cancer in an unscreened population of women aged over 18 years of 5.9 per 10, 000 per year. With 70% coverage and three yearly screening under strategy A, the incidence fell to 2.00 and under B to 2.10. The number of smears required was similar but A required two to three times as many colposcopies as B. Raising the coverage to 90% reduced the incidence to around 1 per 10, 000 per year but changing the screening interval, the specificity or sensitivity of cytology had much less effect. CONCLUSION--The model has been tested under a wide range of possible variations in natural history, specificity and sensitivity of cytology. For low grade smear abnormalities, open colposcopic referral is predicted to reduce invasive cancer only slightly more than repeat cytology, at the expense of much additional colposcopy. Improving cytological coverage is suggested as more effective in reducing invasive cancer than increased use of colposcopy or more frequent screening.